Anti-inflammatory and antioxidant activity of ursolic acid: a systematic review and meta-analysis - Zhao, Man; Wu, Fengyang; Tang, Zhaohong; Yang, Xinyu; Liu, Yanhua; Wang, Fengxia; Chen, Baojiang (Frontiers in Pharmacology, 2023)
There is currently evidence suggesting that ursolic acid may exert a favorable influence on both anti-inflammatory and antioxidant impact. Nevertheless, the anti-inflammatory and antioxidant activities of ursolic acid have not been systematically evaluated. Consequently, this study aims to conduct a systematic review and meta-analysis regarding the impact of ursolic acid on markers of inflammatory and antioxidant activity in both animal models and in vitro systems. The search encompassed databases such as PubMed, Web of Science, Google Scholar, and ScienceDirect, up until May 2023. All eligible articles in English were included in the analysis. Standardized mean differences (SMD) were pooled using a random-effects model, and the included studies underwent a thorough assessment for potential bias. The final review comprised 31 articles. Findings from both animal and in vitro studies suggest that ursolic acid decreases inflammatory cytokine levels, elevates antioxidant enzyme levels, and reduces oxidative stress levels (Figure 1). This meta-analysis furnishes compelling evidence for the anti-inflammatory and antioxidant properties of ursolic acid.